2014
DOI: 10.1177/1060028014522982
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Medication Adherence Report Scale (MARS-5) as a Quantitative Measure of Adherence to Inhalation Medication in Patients With COPD

Abstract: Self-reported adherence measured by MARS-5 is inaccurate in identifying nonadherence to inhalation medication in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 32 publications
2
71
2
3
Order By: Relevance
“…However, our results can only be interpreted in the context of epilepsy treatment, because the MARS-5 score has been found ineffective to accurately reflect medication adherence in patients with other diseases [18,19]. Moreover, after controlling for demographic parameters, we found that seizure severity and serum drug level can correlate well with the MARS-5 score.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, our results can only be interpreted in the context of epilepsy treatment, because the MARS-5 score has been found ineffective to accurately reflect medication adherence in patients with other diseases [18,19]. Moreover, after controlling for demographic parameters, we found that seizure severity and serum drug level can correlate well with the MARS-5 score.…”
Section: Discussionmentioning
confidence: 46%
“…Therefore, there is the need for a reliable self-reporting instrument (e.g., the Medication Adherence Report Scale, MARS-5) which can provide relatively accurate information on AED adherence. Previous studies suggest that the MARS-5 failed to distinguish well-adherent and nonadherent patients with chronic obstructive pulmonary disease [18] and hypertension [19]. However, such poor efficacy may not occur in people with epilepsy because of different clinical characteristics.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, we found that the psychometric evaluation of the MARS-5 has only been done on populations without stroke using classical test theory. 21Y23 Although some studies have argued whether the MARS-5 can accurately measure drug adherence, 24,25 other studies have found that the MARS-5 can accurately measure medication adherence. 26,27 In fact, Lin et al 28 concluded that the unique characteristics of different diseases may contribute to different findings regarding the accuracy of the MARS-5.…”
mentioning
confidence: 99%
“…Research techniques to address adherence with inhaled medication include canister weighing and electronic monitoring of inhaler actuation. Self-reporting is a simple and easy way to assess adherence and is useful in identifying patients' reasons for non-adherence [121], although the accuracy of this method has been questioned [122]. Numbers of filled prescriptions are used as an indicator of adherence/persistence, but again may not reflect medications taken.…”
Section: Remaining Questions and Future Researchmentioning
confidence: 99%